2011
DOI: 10.1111/j.1751-228x.2011.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential Susceptibility in Early Literacy Instruction Through Computer Games: The Role of the Dopamine D4 Receptor Gene (DRD4)

Abstract: Not every child seems equally susceptible to the same parental, educational, or environmental influences even if cognitive level is similar. This study is the first randomized controlled trial to apply the differential susceptibility paradigm to education in relation to children's genotype and early literacy skills. A randomized pretest–posttest control group design was used to examine the effects of the Intelligent Tutoring System Living Letters. Two intervention groups were created, 1 receiving feedback and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 30 publications
(39 reference statements)
3
73
3
Order By: Relevance
“…In one randomized experiment, toddlers who carried this allele showed a greater reduction in disruptive behaviour after parenting skill intervention than children who did not carry this allele 7 . In another experiment, preschoolers with the same genotype were more positively affected by being randomly assigned to exposure to computer games that targeted their emerging phoneme awareness skills than those children not carrying this allele were 8 . In a third trial, this one focused on African-American adolescents and their families, teenagers carrying the 7-repeat version of DRD4 were more positively affected than others by an intervention targeting substance use 9 .…”
mentioning
confidence: 99%
“…In one randomized experiment, toddlers who carried this allele showed a greater reduction in disruptive behaviour after parenting skill intervention than children who did not carry this allele 7 . In another experiment, preschoolers with the same genotype were more positively affected by being randomly assigned to exposure to computer games that targeted their emerging phoneme awareness skills than those children not carrying this allele were 8 . In a third trial, this one focused on African-American adolescents and their families, teenagers carrying the 7-repeat version of DRD4 were more positively affected than others by an intervention targeting substance use 9 .…”
mentioning
confidence: 99%
“…The reading motivation of the fifth graders in this study did not change due to reading in digital format, nor did they learn more new vocabulary than their peers reading hardcopy print books. However, we did find support for the notion that susceptible students benefit from the presence of a pedagogical agent (e.g., Kegel et al, 2011;Plak et al, 2015). Susceptible students who read digital books with guidance from a PA Figure 3.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, accumulating evidence (Kegel et al, 2011;Plak et al, 2015) including the results presented in this article suggest that for a minority of children (carriers of the DRD4 seven-repeat allele) learning outcomes are strongly dependent on the presence or absence of guidance. In the present study, it was shown that guidance provided by a PA helps susceptible students to learn more from reading.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations